Exploring the Pedagogical Impact of Educandy Application in Arabic Language Assessment - K. M. A. AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This study evaluates the effectiveness of the Educandy application as an assessment tool for Arabic language learning among undergraduate students at The New College, Chennai. The research assesses three key aspects: the validity of the media, the validity of the assessment, and the overall matching of questions. Utilizing expert evaluation, statistical reliability tests, and hypothesis testing through SPSS, the study measures the effectiveness of Educandy in enhancing student learning outcomes. The results indicate that while the assessment tool exhibits high reliability (Cronbach's alpha > 0.7), the overall effectiveness of Educandy remains limited. The Gain-N test reveals a 47.86% improvement in learning outcomes, categorizing its effectiveness as "less effective." Hypothesis testing further supports this conclusion, showing no significant difference in performance between the experimental and control groups. Consequently, this study concludes that while Educandy offers engaging features, its effectiveness as an Arabic language assessment tool requires further improvement to achieve optimal learning outcomes.